A new fracture of the forearm adjacent to a healing fracture - Wilson, J. M. (Springer-Verlag, 2000)
A 10-year-old girl sustained closed fractures of the distal radius and ulna. This was manipulated and she was treated in an above-elbow plaster for 4 weeks. Two weeks later she was discharged, only to have a second injury to the same forearm. X-ray showed a new fracture distal to undisrupted callus.